Kajian Ekolinguistik Palantar Bajampi dalam Ritual Kematian Basuayak pada Masyarakat Dayak Kanayatn - Ursula Dwi Oktaviani; Gabriel Serani; Dea Agnes Singgar Sari; Melly Febriani (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study analyzes the palantar bajampi in the basuayak death ritual of the Dayak Kanayatn community in West Kalimantan through an ecolinguistic perspective. It aims to reveal the role of ritual language and plant symbolism in mediating the relationship between humans, nature, and the spiritual world. A qualitative descriptive method was applied through participant observation, audiovisual documentation, in-depth interviews, and field notes. Data were transcribed, translated, and analyzed using a semantic matrix model comprising four elements: social sense, individual meaning, social import, and personal significance. The findings identified two main bajampi processes involving six plants—malakng, jinyalo, tamparengat, porakng, daukng jarikng, and daukng bintawa’ tuha—and kalimabo and rinyuakng leaves soaked in hot water. Both serve to heal grief, dispel nightmares, and appease spirits. The study highlights how ritual lexicon and material culture embody ecological wisdom and cosmological balance, contributing to the preservation of endangered ritual languages.